"Selling TIF: Positioning Hudson Yards as a project that pays for itself". (June 2022) - Fisher, Bridget; Leite, Flávia
Abstract: This research examines how tax increment financing (TIF)'s theoretical ability to pay for itself can be used to camouflage development risks and facilitate project approval, even in a municipality with effective and accountable land use and taxing authorities. The analysis uses a case study of the United States' largest TIF-type project, New York City's Hudson Yards redevelopment project. When proposed, the 3.5 billion public investment in Hudson Yards was sold as self-financing by supporters and elected officials and passed the City Council in 2005 with widespread support. Yet, by documenting the projected and actual costs of implementation over Hudson Yards' first 14 years, the project's first phase cost the city an additional 2.2 billion due to the city's decisions to shift risk from developers onto taxpayers. In light of policy mobility studies' documentation of TIF's global expansion and the use of Hudson Yards as a global model for urban development projects, this viewpoint illustrates the need for transparent risk assignation before project implementation, especially in cities with less robust economies or less formal institutions. Highlights: Policy mobility studies document TIF's expansion beyond the U.S. Few studies evaluate the risks of TIF's use both in the Global North and South. Hudson Yards sold as self-financing but cost New York 2.2 billion extra. TIF's self-financing premise can be used to camouflage risks and costs. Better assignation of TIF risks needed, particularly in less resilient economies.